ANALYSIS OF BRIGUNA DIGITAL INFORMATION SYSTEM IMPLEMENTATION IN IMPROVING BRIGUNA CREDIT EFFICIENCY AT BRI SRIWIJAYA BRANCH OFFICE - Ismi, Ismi Melyana; Fathiyah Nopriani (International Journal of Multidisciplinary Reseach, 2026)
This study analyzes the implementation of the Briguna Digital Information System in improving credit efficiency at the Bank Rakyat Indonesia (BRI) Sriwijaya Branch. The rapid advancement of information technology has driven the banking industry to adopt digital systems to enhance operational effectiveness, data accuracy, and service quality. The main issue addressed in this research is the inefficiency of manual credit processes, which previously required long processing times and caused high administrative workloads. The purpose of this research is to determine how the implementation of Briguna Digital contributes to enhancing the efficiency of Briguna credit services in terms of processing speed, data accuracy, employee performance, and customer satisfaction. This study employs a descriptive qualitative method, using observation, interviews, and documentation as data collection techniques. The results show that Briguna Digital significantly reduced the average credit processing time from 5–7 working days to 2–3 days, decreased data entry errors by 41%, and improved customer satisfaction by 35%. The system also increased employee productivity by minimizing manual verification and paperwork through integrated digital processing. Despite these improvements, challenges remain, including limited digital literacy among senior employees and occasional network instability. Overall, Briguna Digital supports BRI’s digital transformation strategy by creating a more efficient, transparent, and technology-driven banking service model that aligns with the national goal of strengthening financial inclusion through digital innovation.